Emotions as testimony: Documenting the psychological aspects of witnessing in an early survivor historical commission - Victoria Van Orden Martínez (Zagłada Żydów)
In 1945–1946, nine Polish former prisoners of Nazi concentration camps (one Jewish and eight non-Jewish) living in Sweden as refugees were employed to record other Jewish and non-Jewish Poles’ experiences of persecution for history and justice. Although none of these individuals were psychologists, they believed recording the psychological aspects of witnessing was essential to their documentation work. The written testimonies they recorded, which are preserved in the archive of the Polish Research Institute in Lund, Sweden (PIZ), thus include revealing and often caring comments about the witnesses’ emotions and emotional responses during the interviews. I argue that this method made emotions integral to the testimonies and validated emotions as testimony. The significance of this argument is magnified when non-Jewish Poles interviewed Jewish Poles and vice versa since the comments reveal how they were relating to one another on a personal and sensitive level. This article builds on the author’s previous and ongoing analyses of these witness testimonies through close readings of the comments that consider the psychological aspects of witnessing. By contextualizing these comments and the testimonies they refer to alongside theories on the value of emotions for knowledge, the author explores what knowledge the method of recording witness testimonies contributed to creating in the early postwar period and what knowledge it creates now.